EFFECT OF SEED PRIMING BY KH2PO4 AND DIFFERENT TEMPERATURE ON SEEDS GERMINATION BEHAVIOR OF OKRA (Abelmoschus esculentus L.) - Sahib, et.al, Muhannad.M. (Al-Qadisiyah Journal of Pure Science, 2017)
In order to evaluate the effect of seed priming techniques on seeds germination characteristics of Okra. an experiment was conducted at the Seeds obtained directly from the field of Babil governorate during the season of (2012-2013). Seeds were primed for 4 hours at two temperatures (25 and 30 CÂº) in priming media (1.5% and 3% KH2PO4, and hydropriming, distilled water as control). Maximum seed germination percentage, germination speed index (GSI), seedling vigour index (SVI), was observed when the seeds primed by KH2PO4 3% for 4h and at 20 and 30 CÂº. Relative growth rate and all seeds germination characteristics in this study also increasing with increased KH2PO4 concentration from 1.5 to 3% compared to control